Finite mathematics with applications in the management, natural, and social sciences - Lial, Margaret L.; Hungerford, Thomas W.; Holcomb, John P. Jr; Mullins, Bernadette (Pearson Education Limited, 2015)
Finite Mathematics with Applications in the Management, Natural, and Social Sciences presents sound mathematics in an understandable manner, proceeding from the familiar to new material and from concrete examples to general rules and formulas. The Eleventh Edition retains its focus on real-world problem solving, but has been refreshed with revised and added content, updated and new applications, fine-tuned and newly-integrated pedagogical devices, and enhanced exercise sets. The new edition supports students with a tightly integrated MyMathLab (R) course and quality applications and exercises.